The Search for Meaning: continuing Problems with the Interpretation of Treaties - McRae, Peter (Victoria University of Wellington Law Review, 2002)
This paper argues that old controversies regarding the objects and methods of treaty interpretation have not been resolved by the coming into force of articles 31 and 32 of the Vienna Convention on the Law of Treaties 1969. The articles, it is argued, have not so much resolved previous debates between "schools" of interpretation, as obscured them under an apparently clear regime, while interpreters continue to adopt their own preferences. The paper describes the three main schools – textualist, intentions of the parties, and teleological – and concludes none offers a satisfactory scheme by itself. It then examines the development of the Convention articles, and concludes they represented a compromise in which the drafters failed to resolve the key issue of the underlying purpose or object of interpretation. It then shows that an orthodox interpretation of the articles has developed, which assumes they embody the textualist position. The paper then discusses how this orthodoxy has been accepted by the majority of the International Court of Justice in the 1990s, but with significant dissent drawing on insights from especially an intentions of the parties approach. The paper then draws on insights from modern approaches to the interpretation of commercial contracts, to suggest that the best resolution of the "text versus intentions" dichotomy lies in accepting that establishing the actual intentions of parties is the purpose of interpretation, and that therefore an apparently clear text will be strong but not conclusive evidence of such intentions. The paper examines how this refinement would have helped to resolve difficult interpretations before the ICJ, and concludes that such an approach is both desirable and consistent with articles 31 and 32.